Description Of Increased Uric Acid Levels In Ujung Tanduk Village Communities Before And After Drinking Tuak - Hepni; Fitri Yanti; Selya Pangaribuan (International Journal of Health Engineering and Technology, 2023)
Tuak is a type of alcoholic drink made from palm sugar. Continuous excessive consumption of palm wine can increase uric acid levels in the body. Uric acid is part of purine metabolism, but if metabolism occurs abnormally there will be a process of accumulation of uric acid crystals in the joints which causes quite high levels of pain such as joint disorders (Gouty arthritis). The aim is to determine the description of uric acid levels before and after consuming palm wine in residents in Ujung Tanduk Village, Laguboti District. The research that will be used is a quantitative type of research with a descriptive research design, with a purposive sampling technique. The results showed that 8 research samples, 2 people (25%) of the sample consuming 4 glasses of palm wine experienced a decrease in uric acid levels with an average of 0.25 mg/dl, 4 people (50%) of the sample consuming 6 glasses of palm wine experienced an increase in uric acid levels with an average of 0.4 mg/dl, and 2 people (25%) of the sample who consumed 8 glasses of palm wine experienced an increase in uric acid levels with an average of 1.25 mg/dl. Consuming too much palm wine can increase uric acid, therefore reducing the frequency of consuming palm wine can reduce uric acid levels.